Assessing climate change impacts on flood risk in the Yeongsan River Basin, South Korea - Agbortoko Bate Ashu; Junsuk Kang (Scientific Reports)
Abstract Flood risk prediction is critical for adaptation to the forecast frequency of extreme weather events. As South Korea experiences events that cause widespread flood damage, we conducted a flood risk assessment by employing global climate models and a hydrological model of the Yeongsan River Basin. Using shared socioeconomic pathway scenario data from the soil and water assessment tool, we simulated daily streamflow and reservoir outflow data for each sub-basin, modeling baseline, mid-century, and end-century scenarios. Four flood indices (duration, magnitude, probability, and frequency) were used for estimating flood risk. The spatial distribution of flood risk projected higher risks in most sub-basins for the mid- and end-century scenarios with an increase of flood amount to about 65% in the future. Adaptive strategies were required to address the risks of both flash floods and longer-term flooding. The study facilitates prioritizing flood risk regions for implementing effective preventive measures and efficient flood management.